STUDY OF PAREMIOLOGICAL UNITS IN WORLD LINGUISTICS (Intent Research Scientific Journal, 2024)
Paremiological units are widely used in society since ancient times. In ancient times, people did not have the opportunity to put their thoughtsin written form. They had to remember catchy sayings similar to the paremiological units. Consequently, such sayings as the norm of society were spread orally from generation to generation, and subsequently renamed as "paremia" or "paremiological unit". "Paremiological unit" is the scientific meaning, while this name is widely spread among the people as “proverbs and sayings”. Soviet folklorist G.L. Permyakov gives the following comment on proverbs: "First of all proverb and saying is a language phenomenon, consisting of regular expressions similar to phrases. Secondly, they are logical units representing certain meanings. Thirdly, proverb and saying is an artistic miniature with the most remarkable example of truth data collection." (Permyakov G.L., 1988).Paremiological units or paremia are stable in the language. They can be characterized by rhythm, brevity, stability, standards, emotional intensity, imagery, artistic and regular expression of their originality, their unique inhesion to the people and their long-term effectiveness.